GAMBARAN KARAKTERISTIK PETUGAS PENDISTRIBUSIAN BERKAS REKAM MEDIS RAWAT JALAN DI UPT RUMAH SAKIT KHUSUS PARU TAHUN 2019 - Ali Sabela Hasibuan (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
One form of service at the hospital is the distribution of medical record files. Distribution is a process of delivering goods or services from producers to consumers and users, when the goods or services are needed. The purpose of this study was to determine the distribution of outpatient medical record files at the UPT Special Paru Hospital in 2019. This study used a descriptive research method with the aim of making an objective description or description of a situation with a total population of all medical record staff employees, namely 5 people and the sampling technique in this study is total sampling with the characteristics of all medical record officers. So the researchers analyzed the data starting from editing, coding, sorting, data entry, cleaning. The results of the study based on the majority of high school education were 3 people (60%) minority DIII medical records as many as 1 person (20%) and S1 education as many as 1 person (20%), based on the majority of 1-5 years working duration as many as 4 people ( 80%), and a minority of 6-10 years of work as many as 1 person (20%). So it can be concluded that the implementation of the distribution of outpatient medical record files is said to be sufficient, the length of the process of distributing medical record files and there are still a few medical record officers who are educated in DIII medical records and can be expected to improve the process of sending medical record files and the addition of officers with DIII medical record education.